The Structure of School Textbook as an Object of Academic Research (With a New Type of Russian Language Textbook as an Example) - Granik G.G (Moscow State University of Psychology and Education, 2017)
The paper reviews the problem of the structure and functions of the Russian language textbook in a retrospective aspect.A critical analysis of psychological and didactic research in this field revealed that, despite a significant number of published works, the question of the scientifically grounded structure and functions of the textbook has not been resolved.The structure of textbooks of a new type described in the paper was developed basing on the systematization and generalization of psychodidactic knowledge as well as on the fundamental and individual studies carried out by the authors of these textbooks.The paper outlines the key principles of this Russian language course developed for students of 1st-9th grades.This course is built on a syntactic basis and is designed not as concentric circles, like the existing textbooks, but as an expanding spiral.The paper reviews the structural components of the textbook (theoretical linguistic texts, theoretical psychodidactic texts, fiction texts and educational texts of the tasks) which are aimed at forming the psychological mechanisms of literate oral and written speech in schoolchildren, at developing their text comprehension skills, awakening their emotions through reading.The paper concludes with examples of some structural components of the textbook.